The videoconference as an educative tool: what should be considered? - Reinoso-González, Eduardo (Spanish Journal of Medical Education, 2020)
Currently, education is faced with a global health crisis that has put the continuity of teaching processes in check, the spread of the SARS COV-2 virus is affecting most of the population due to its high contagion capacity, which has led to taking as a main measure the confinement of people and the closure of places with high attendance such as schools and universities. As a result of this, the internet has assumed prominence as the most used digital technology and communication tool in the world, being in turn, the main resource for the execution of videoconferences, which have taken a unique role in the training of students higher level in synchronous e-learning modality, due to health contingency. By virtue of this, what should we consider when implementing videoconferences?